Causal relationship between the global foreign exchange market based on complex networks and entropy theory. (June 2017) - Cao, Guangxi; Zhang, Qi; Li, Qingchen
Highlights: Mutual information is used as the edge weights of nodes instead of PCC, which overcomes the shortcomings of linear correlation functions. SGD turns into a new cluster center and gradually becomes a point connecting the Asian and European clusters during and after the US sub-prime crisis. Liang's entropy theory, which has not been adopted before in the global foreign exchange market, is considered. Abstract: The foreign exchange (FX) market is a typical complex dynamic system under the background of exchange rate marketization reform and is an important part of the financial market. This study aims to generate an international FX network based on complex network theory. This study employs the mutual information method to judge the nonlinear characteristics of 54 major currencies in international FX markets. Through this method, we find that the FX network possesses a small average path length and a large clustering coefficient under different thresholds and that it exhibits small-world characteristics as a whole. Results show that the relationship between FX rates is close. Volatility can quickly transfer in the whole market, and the FX volatility of influential individual states transfers at a fast pace and a large scale. The period from July 21, 2005 to March 31, 2015 is subdivided into three sub-periods (i.e., before, during, and after the US sub-prime crisis) to analyze the topology evolution of FX markets using the maximum spanning tree approach. Results show that the USD gradually lost its core position, EUR remained a stable center, and the center of the Asian cluster became unstable. Liang's entropy theory is used to analyze the causal relationship between the four large clusters of the world.